Let´s learn english in a communicative way - Macas, Elizabeth; Ríos, María
This project has been conceived as a useful tool for teachers and students. It emerged due to the learning problems presented in the students of ninth level of Basic Education of Luisa de Jesus Cordero High School. The majority of students are frightened in participating in oral practice, this affecting the development of their speaking skill. Because of this problem, we propose to apply new strategies and innovating didactic resources related to the development of this speaking skill in order to raise the interest of the students and encourage them to use the language to communicate in the classroom taking into account their particular background and needs. The activities proposed are full of visual aids, which will help them participate in a freer way with meaningful learning. The activities will be varied and will occupy the students´ attention and interest during the whole teaching-learning process. At the end of this work we present some of the activities that can be developed in class. We have seen that the use of these activities promote the students´ commitment in their own learning and advice colleague teachers to use these activities in their schools.